2019
DOI: 10.1002/ente.201901105
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar V5O12·6H2O Nanobelts Coupled with Inert Zn(OH)2·0.5H2O as Cathode for Aqueous Zn2+/Nonaqueous Na+ Storage Applications

Abstract: Lamellar V5O12·6H2O nanobelts coupled with inert Zn(OH)2·0.5H2O are in situ fabricated via a facile hydrothermal strategy. Herein, the inert Zn(OH)2·0.5H2O phase acts as a buffer matrix to strengthen the structural stability of V5O12·6H2O host material, relieving the severe volume variation. Therefore, benefiting from the large interplanar spacing of active V5O12·6H2O and volume buffering effect of inert Zn(OH)2·0.5H2O, V5O12·6H2O/Zn(OH)2·0.5H2O hybrid (denoted as Z‐V5O12·6H2O) sustainably endures the repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The results revealed that cathodes with high mass loading exhibited poor rate performance, which demonstrated that thick cathodes restricted the pseudo-Zn-air reaction and the diffusion of Zn 2 + . To alleviate the severe capacity decay of V x O y electrodes, Ru et al [94] devised an innovative method to prepare Recently, Wang et al [95] got a new approach based on the ability to substantially increase the electrochemical capacity of aqueous Zn/V 5 O 12 • 6H 2 O cells by adding a small amount of platinum (Pt, 1.5 wt.%). Given their previous work, [93] the electrochemical performance was enhanced by adjusting the quantities of oxygen-containing functional groups on the GO surface.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that cathodes with high mass loading exhibited poor rate performance, which demonstrated that thick cathodes restricted the pseudo-Zn-air reaction and the diffusion of Zn 2 + . To alleviate the severe capacity decay of V x O y electrodes, Ru et al [94] devised an innovative method to prepare Recently, Wang et al [95] got a new approach based on the ability to substantially increase the electrochemical capacity of aqueous Zn/V 5 O 12 • 6H 2 O cells by adding a small amount of platinum (Pt, 1.5 wt.%). Given their previous work, [93] the electrochemical performance was enhanced by adjusting the quantities of oxygen-containing functional groups on the GO surface.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…94 %/1000/2 A g À 1 33 [92] V 5 O 34 [93] ZÀ V 35 [94] V 5 O -/400/10 A g À 1 36 [95] V 6 O 43 [104] VCF 3 M Zn(CF…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…. [103] Owing to the buffering effect of inert Zn(OH) 2 •0.5H 2 O, repeated insertion/extraction of Zn 2+ can be tolerated continuously, thereby relieving serious volume changes. Different from the reported lamellar vanadium oxides, Li et al synthesized novel heterogeneous vanadium oxide nanowires with a V 2 O 5 •nH 2 O shell and a V 3 O 7 •H 2 O nucleus, and called h-VOW.…”
Section: Othersmentioning
confidence: 99%